Intrathecal Silymarin Administration Improves Recovery After Compression Spinal Cord Injury: Evidence for Neuroprotection, Antioxidant, and Anti-Inflammatory Action - Echeverria-Morgado, J (Frontiers Media SA, 2025)
Background: Spinal cord injury (SCI) is a debilitating disorder that affects people’s quality of life. Unfortunately, there is no definitive drug for treating SCI. Additionally, the adverse effects of existing non-approved drugs make it necessary to research and investigate the effects of new multi-target agents to combat SCI complications. Purpose: This study specifically investigates the effect of a multi-target phytochemical silymarin (SIL), known for its potent neuroprotective, anti-inflammatory, and antioxidant properties, on sensorimotor function after SCI. Materials and Methods: In total, 30 male Wistar rats were divided into five distinct groups: Sham, SCI, and three additional groups that received SIL at dosage levels of 0.1, 0.2, and 0.4 μmol. Following the injury, behavioral tests such as acetone drop, hot plate, von Frey, BBB, and inclined plane were conducted along with weight measurements for 4 weeks. Serum samples were analyzed to assess alterations in catalase and glutathione levels, nitrite concentration, and the activity of matrix metalloproteinases (MMP) 2 and 9. Besides, histopathological studies were done to evaluate the number of neurons in the spinal cord tissue. Results and discussion: Various doses of SIL, particularly the 0.2 μmol dosage, significantly influenced the alleviation of pain, enhancement of motor function, and weight gain in animals following SCI. In addition, SIL increased the levels of catalase and glutathione, while decreasing serum nitrite levels. It also increased anti-inflammatory MMP2 levels and the sensory/motor neurons’ survival, while decreasing inflammatory MMP9. Conclusion: Generally, intrathecal injection of SIL after SCI provides neuroprotective, anti-inflammatory, and antioxidant effects leading to pain reduction and improved motor function in rats. © © 2025 Bahmani, Kiani, Fakhri, Abbaszadeh, Rashidi and Echeverría.